Genomics-based strategies for the use of natural variation in the improvement of crop metabolism. (January 2016) - Scossa, Federico; Brotman, Yariv; de Abreu e Lima, Francisco; Willmitzer, Lothar; Nikoloski, Zoran; Tohge, Takayuki; Fernie, Alisdair R.
Highlights: We present an overview of genetic variation that can underlie metabolism in crop species. We review the use of introgression breeding and detail the wild relatives of our crops which can be used for this purpose. Information emanating from metabolite quantitative trait loci approaches is detailed. The advances afforded by multiple plant genomes are highlighted. Abstract: Next-generation genomics holds great potential in the study of plant phenotypic variation. With several crop reference genomes now available, the affordable costs of de novo genome assembly or target resequencing offer the opportunity to mine the enormous amount of genetic diversity hidden in crop wild relatives. Wide introgressions from these wild ancestors species or land races represent a possible strategy to improve cultivated varieties. In this review, we discuss the mechanisms underlying metabolic diversity within plant species and the possible strategies (and barriers) to introgress novel metabolic traits into cultivated varieties. We show how deep genomic surveys uncover various types of structural variants from extended gene pools of major crops and highlight how this variation may be used for the improvement of crop metabolism.